Obstetric violence: Physical and psychological impacts on women’s lives - A narrative of reports and after-effects (Research, Society and Development, 2024)
The experience of childbirth is often characterized by pain, suffering, embarrassment and aggression. This is because, in addition to unnecessary and/or painful interventions, scientifically unsustainable restrictions and professional attitudes that constitute obstetric violence, whether physical, psychological or verbal, are also common. The aim of this study is to understand and report on the experience of a woman who was a victim of obstetric violence, its events and its physical and psychological consequences. It also aims to develop an information booklet to disseminate information to pregnant women from prenatal care onwards. This qualitative study is based on a descriptive, exploratory case report. The study included the participation of a woman who had experienced violence during childbirth, which consequently served as the basis for this study. The methodology used to collect information was a questionnaire developed by the authors and applied in person, which contained 47 questions divided into three blocks: prenatal, childbirth and postpartum. In the research participant's account of the moments she experienced during labor, the practices, pain and suffering resulting from the lack of information about her rights during childbirth are noticeable. The consequences of obstetric violence can leave marks that last for years, physical as well as psychological trauma.